Incorporating the Future: Optimizing Cybersecurity through Seamless Integration of Artificial Intelligence - Muhammad Asif Ibrahim; Syed Khurram Hassan (International Journal for Electronic Crime Investigation, 2023)
Cyber-attacks are becoming more sophisticated and common in today’s environment. Artificial intelligence (AI) is being used by enterprises to boost their defenses against these developing threats. AI is rapidly altering the cybersecurity field, providing several benefits in terms of improving security measures. However, its implementation causes significant changes in cybersecurity occupations and necessitates the acquisition of new skills by specialists. This article investigates the impact of AI on cybersecurity employment, presents real-world instances of AI integration in the sector, analyzes the future of AI in cybersecurity, and identifies the problems nvolved with its adoption.